2017
DOI: 10.1002/zamm.201700236
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity of two‐dimensional composites with randomly distributed elliptical inclusions

Abstract: Analytical approximate formulae for the effective conductivity tensor of the two-dimensional composites with elliptical inclusions are derived in the form of polynomial approximations in concentration. New formulae explain the seeming contradiction between various formulae derived in the framework of self consistent methods. Random composites with high conducting inclusions of two different shapes (elliptical and circle) of the same area are compared. It is established that greater relative concentration of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Different approxmate formulae/solutions for the mathemat-ical model hold under restrictions usually not discussed by authors. A serious methodological mistake may follow when intermediate manipulations are valid only within the precision O(f ), while the final formula is claimed to work with a higher precision, see an explicit example in [22]. In particular, it follows from our formulae (5.21)- (5.22) that it is impossible to write a universal higher order formula independent on locations of inclusions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Different approxmate formulae/solutions for the mathemat-ical model hold under restrictions usually not discussed by authors. A serious methodological mistake may follow when intermediate manipulations are valid only within the precision O(f ), while the final formula is claimed to work with a higher precision, see an explicit example in [22]. In particular, it follows from our formulae (5.21)- (5.22) that it is impossible to write a universal higher order formula independent on locations of inclusions.…”
Section: Discussionmentioning
confidence: 98%
“…We can say that it is certainly methodological, not a computational error, related to intuitive physical investigation of the conditionally convergent integral discussed in [7]. The critical review of the limit transition from finite to infinite number of inclusions in applications of self-consistent and cluster methods is presented in [8,20,21,22] for 2D conductivity problems. In particular, it was demonstrated that self-consistent and cluster methods with various intuitive corrections are frequently applied within the accuracy f , but the obtained results are applied to high concentrations without any justification.…”
Section: Introductionmentioning
confidence: 99%